Pengelolaan dan Perlindungan Kawasan Pesisir - Handri Jurya Parmi (Mandala, 2019)
Indonesia has a lot of potential such as marine potential, where since the enactment of Law Number 5 of 1983 concerning the Indonesian Exclusive Economic Zone claims that the sea area is 200 miles wide, this adds to the jurisdiction of Indonesian waters as much as 2.7 million km2, therefore it is not surprising if Indonesia is known as an archipelago. In accordance with the nature of the Unitary State of the Republic of Indonesia as a rule of law, the development of a system of management of Coastal Areas and Small Islands as part of sustainable development that has environmental insight must be given a clear, firm and comprehensive legal basis to ensure legal certainty for efforts to manage the Territory Coastal and Small Islands then with the approval of the House of Representatives of the Republic of Indonesia and the President LAW No. 27 of 2007 concerning management of coastal areas and small islands. The legal basis is based on Pancasila and the 1945 Constitution to protect the natural resources contained in Indonesia are state obligations and state duties. This is stated in the Indonesian constitution, namely Article 33 paragraph (3) of the fourth Amendment of the 1945 Constitution which states that the earth and water and the wealth contained therein are controlled by the state, and are used for the greatest prosperity of the people. Based on this background and the results of a review of legislation (20 national laws) and conventions (5 international conventions) that the Indonesian government has ratified relating to the management of coastal areas, the government and the legislature form Law Number 27 Year 2007 concerning Management of Coastal Areas and Small Islands. On June 26, 2007, in its General Assembly, the Indonesian Parliament passed the Law on Management of Coastal Areas and Small Islands (PWP3K). In one chapter, chapter V regulates the utilization given in the form of coastal water concession rights, which is regulated in Article 16 up to Article 22. Management of integrated coastal areas (Integrated Coastal Zone Management or abbreviated as ICZM). Protection and management of coastal areas and small islands are regulated in Article 16 up to Article 20 of Law Number 27 of 2007 concerning Management of Coastal Areas and Small Islands, namely:: utilization is given in the form of HP-3 covering sea level and water ponds up to the surface of the sea floor, HP-3 is given in a certain area and time, must pay attention to the preservation of ecosystems, indigenous peoples, national interests, and peaceful crossing rights for foreign vessels, HP-3 is given to individuals, legal entities, and communities adat, granted for a period of 20 years and can be extended up to twice, HP-3 can switch, be transferred and become collateral for debt